Sistem Informasi Manajemen Operasional Bongkar Muat Container Berbasis Web pada PT. Prima Indonesia Logistik Belawan - Rizky Imam Muda; Yursal Yursal; Irma Handayani (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This paper discusses the WEB-based container loading and unloading operational management system at PT. Prima Indonesia Logistics Belawan. Several obstacles in the operational management information system for loading and unloading containers include electricity disturbances which prevent containers from entering the depot area and drivers who do not pay attention to the job orders being carried. The aim of this research is to understand how the operational management information system for loading and unloading containers works. This research uses field research methods, which involve direct observation and discussion with the company, as well as library research using books in the Medan Indonesian Maritime Adiguna Polytechnic library and other relevant reading sources. In conclusion, the web-based container loading and unloading operational management information system at PT. Prima Indonesia Logistics Baelawan has generally been implemented well and according to procedures, however there are still problems due to electrical disturbances which prevent containers from entering the get in area..